The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.bja.2020.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating interventions to reduce the risk of postoperative delirium

Abstract: Rapid rampup of powered air-purifying respirator (PAPR) training for infection prevention and control during the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
(24 reference statements)
0
5
0
2
Order By: Relevance
“…After long years of use, it has come to the fore with an important side effect defined in recent years: "postoperative delirium". 2,8 It is said that 57% of patients are affected by delirium and this causes longer ICU and hospital stays after cardiac surgery. 8 With an increasing demand for intensive cardiovascular and ventilatory support during the immediate postoperative period, the "fast-tracking cardiac anesthesia" term has emerged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After long years of use, it has come to the fore with an important side effect defined in recent years: "postoperative delirium". 2,8 It is said that 57% of patients are affected by delirium and this causes longer ICU and hospital stays after cardiac surgery. 8 With an increasing demand for intensive cardiovascular and ventilatory support during the immediate postoperative period, the "fast-tracking cardiac anesthesia" term has emerged.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, midazolam has been shown to cause a high rate of postoperative delirium, and prolonged ICU stays in cardiac surgery patients. 2 Fast track and balanced anesthesia protocols have been developed in years for all these reasons. The balanced anesthesia methods are provided with a sedative-hypnotic agent with a low side-effect profile, as well as opioids with a short duration of action and volatile anesthetics.…”
Section: The Effects Of Conventional and Balanced Anesthesia Protocol...mentioning
confidence: 99%
“…Delirious patients often remove intubation and infusion tubes from the body, which seriously threatens the safety of patients' lives. For the occurrence of postoperative delirium, current research has confirmed many factors including major bleeding during surgery, hemodynamic instability, and the patient's history of cerebrovascular disease [47][48][49][50][51] . However, there is still a lack of a systematic and effective prediction system, thence it is of great significance to explore and study the prediction scoring system for delirium following OPCABG.…”
Section: Discussionmentioning
confidence: 99%
“…El DPO es una de las complicaciones frecuentes de la cirugía. Ocurre hasta en un 65% de los pacientes de todas las edades, siendo este porcentaje dependiente del tipo de cirugía (mayor incidencia en cirugías mayores y de emergencia frente a las cirugías menores y electivas) y del procedimiento al cual se va a someter el paciente, así como de la edad de este, ya que el DPO es más frecuente en adultos mayores (> 65 años), lo cual es un gran problema sanitario, debido a que más de un tercio de las cirugías realizadas en pacientes ingresados en un centro hospitalario ocurren en este grupo etario (1,7,(12)(13)(14)(15). Los adultos mayores, al ser sometidos a cirugía, se encuentran en un riesgo del 15-53% de presentar DPO; dicho porcentaje aumenta hasta un 70-87% si el paciente requiere ser admitido en una unidad de cuidados intensivos (1,3,4,9).…”
Section: Epidemiologíaunclassified
“…Igualmente, el uso de dexmedetomidina, la restricción del uso de medicamentos anticolinérgicos, una analgesia óptima y evitar la polifarmacia, han demostrado una reducción en la incidencia del DPO (1,4,5,7,11,(13)(14)(15).…”
Section: Prevenciónunclassified